1999
DOI: 10.1590/s0101-81751999000400020
|View full text |Cite
|
Sign up to set email alerts
|

A field comparison of two capture-mark-recapture estimators of small mammal populations

Abstract: ABSTRACT. The results obtained by two estimators of population sizes, MNKA and Mh, were compared for four species of sma ll mammmais -Didelphis ol/rito Wied, 1826, Philollder /relloto (O ilers, 1818), NectolllYs sql/olllipes (Brants, 1827) and Akodon cursor (Wi nge, 1887) -during a long-te rm population study. The MNKA estimator consistently underestimated the population sizes in relation to Mh. On the other, the probabilistic estimator Mh, which reduces bias through the jackknife technique, cOllld not be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
(13 reference statements)
0
8
0
4
Order By: Relevance
“…On the other hand, there are difficulties in the application of probabilistic models for closed populations because they require more data and cannot be used in many cases (Gentile and Fernandez, 1999). Open population models are then preferred, especially the deterministic ones (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are difficulties in the application of probabilistic models for closed populations because they require more data and cannot be used in many cases (Gentile and Fernandez, 1999). Open population models are then preferred, especially the deterministic ones (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The precise estimation of abundance, incorporating variable probabilities of capture, requires large amounts of data to satisfy the assumptions of probabilistic methods (GENTILE & FERNANDEZ 1999, SLADE & BLAIR 2000. Because obtaining the recommended sample size (50-200 individuals per taxon, depending on the capture probabilities; OTIS et al 1978) from capture-mark-recapture data for mammals is difficult, primarily due to low local abundances and/or low capture/recapture rates, enumeration estimators of population size, such as the MNA, are still widely used in small mammal population studies, especially in the tropics (CROUZEILLES et al 2010, GENTILE et al 2004, LIMA et al 2006, MESERVE et al 2001, YUNGER et al 2002.…”
mentioning
confidence: 99%
“…Studies comparing probabilistic estimators with the MNA have shown that the enumeration estimator produces biased estimates when heterogeneity among individuals and behavioral responses to traps (trap shyness or trap happiness) are present and when capture probabilities are low (BOULANGER & KREBS 1994, EFFORD 1992, GENTILE & FERNANDEZ 1999, HILBORN et al 1976, NICHOLS & POLLOCK 1983. Simple counts are sometimes selected over probabilistic estimators because they are easier to obtain, even though they may underestimate the actual abundance.…”
mentioning
confidence: 99%
“…Além disso, aumentou de abundância após fogo, que extinguiu várias espécies localmente (Pires et al 2004, Figueiredo e Fernandez 2004, o que indica sucesso em áreas perturbadas. Foi mais freqüente em ambientes com alta densidade de arbustos próximos ao chão e alta densidade de serrapilheira (Gentile e Fernandez 1999), foi capturada em área de solo encharcado coberta por vegetação rasteira espaçada no Espírito Santo (Paresque et al 2004), e em bordas de fragmentos e áreas cobertas por bambus no Distrito Federal (Nitikman e Mares 1987). Existem vários outros registros em ambientes alterados (Lessa et al1999.…”
Section: Caracterização Do Uso De Habitats No Planalto Atlântico De Sunclassified
“…Em outras regiões da Mata Atlântica foi capturada em fragmentos florestais (D'Andrea et al 1999, Gentile e Fernandez 1999, Pires et al 2002 …”
Section: Caracterização Do Uso De Habitats No Planalto Atlântico De Sunclassified